Investigations of VOCs in and around buildings close to service stations. (January 2018) - Hicklin, William; Farrugia, Pierre S.; Sinagra, Emmanuel
Abstract: Gas service stations are one of the major sources of volatile organic compounds in urban environments. Their emissions are expected not only to affect the ambient air quality but also that in any nearby buildings. This is particularly the case in Malta where most service stations have been built within residential zones. For this reason, it is important to understand the dispersion of volatile organic compounds (VOCs) from service stations and their infiltration into nearby residences. Two models were considered; one to predict the dispersion of VOCs in the outdoor environment in the vicinity of the service station and another one to predict the filtration of the compounds indoors. The two models can be used in tandem to predict the concentration of indoor VOCs that originate from a service station in the vicinity. Outdoor and indoor concentrations of VOCs around a service station located in a street canyon were measured, and the results used to validate the models. Predictions made using the models were found to be in general agreement with the measured concentrations of the pollutants. Highlights: A model describing the distribution of VOCs around a service station is presented. The indoor VOC concentration due to outdoor and indoor sources is also modelled. The models are tested using measurements made in a street canyon. An estimate of VOC concentration indoors due to a service station can be obtained.